Interorganelle Communication: Peroxisomal MALATE DEHYDROGENASE2 Connects Lipid Catabolism to Photosynthesis through Redox Coupling in Chlamydomonas. Issue 8 (11th July 2018) - Kong, Fantao; Burlacot, Adrien; Liang, Yuanxue; Légeret, Bertrand; Alseekh, Saleh; Brotman, Yariv; Fernie, Alisdair R.; Krieger-Liszkay, Anja; Beisson, Fred; Peltier, Gilles; Li-Beisson, Yonghua
Abstract : Knockout of the peroxisomal MALATE DEHYDROGENASE2 drastically alters photosynthesis and the metabolism of fatty acids and starch upon nitrogen deprivation and high light exposure in the green microalga Chlamydomonas reinhardtii . Abstract: Plants and algae must tightly coordinate photosynthetic electron transport and metabolic activities given that they often face fluctuating light and nutrient conditions. The exchange of metabolites and signaling molecules between organelles is thought to be central to this regulation but evidence for this is still fragmentary. Here, we show that knocking out the peroxisome-located MALATE DEHYDROGENASE2 ( MDH2 ) of Chlamydomonas reinhardtii results in dramatic alterations not only in peroxisomal fatty acid breakdown but also in chloroplast starch metabolism and photosynthesis. mdh2 mutants accumulated 50% more storage lipid and 2-fold more starch than the wild type during nitrogen deprivation. In parallel, mdh2 showed increased photosystem II yield and photosynthetic CO2 fixation. Metabolite analyses revealed a >60% reduction in malate, together with increased levels of NADPH and H2 O2 in mdh2 . Similar phenotypes were found upon high light exposure. Furthermore, based on the lack of starch accumulation in a knockout mutant of the H2 O2 -producing peroxisomal ACYL-COA OXIDASE2 and on the effects of H2 O2 supplementation, we propose that peroxisome-derived H2 O2 acts as a regulator of chloroplast metabolism. We conclude that peroxisomal MDH2 helps photoautotrophs cope with nitrogen scarcity and high light by transmitting the redox state of the peroxisome to the chloroplast by means of malate shuttle- and H2 O2 -based redox signaling.